First insights into herbivore–plant interaction of the spurge hawkmoth and Euphorbia cyparissias - Fiedler, Stephanie; Langner, Mathias; Oertel, Reinhard; Vassão, Daniel G.; Nitschke, Julia; Gershenzon, Jonathan; Hundsdoerfer, Anna K. (Frontiers in Ecology and Evolution, 2023)
The spurge hawkmoth Hyles euphorbiae (Lepidoptera, Sphingidae) is an insect herbivore feeding exclusively on spurges (Euphorbia). These are toxic due to their secondary metabolites including diterpene esters with numerous harmful biological activities, preventing their use by most herbivores. We report for the first time the finding of the tigliane (phorbol ester) phorbol-13-acetate and two putative tiglianes of unknown structure (compounds 2 and 3) in cypress spurge (Euphorbia cyparissias L.), the main larval food plant in Central Europe. Distribution of the three reported compounds within the cypress spurges plant parts (leaves, stem and root) were analyzed to gain first insights into the metabolite conditions H. euphorbiae copes with in nature. Our results indicate different distribution patterns for each compound and that the occurrence of the putative tigliane “compound 3” rises upon larval feeding on the plant. Finally, the presence of the plant-derived tigliane diterpenes in frass from E. cyparissias leaves feeding larvae is confirmed.